2017
DOI: 10.1371/journal.pone.0171720
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of laboratory and daily energy expenditure estimates from consumer multi-sensor physical activity monitors

Abstract: Wearable physical activity monitors are growing in popularity and provide the opportunity for large numbers of the public to self-monitor physical activity behaviours. The latest generation of these devices feature multiple sensors, ostensibly similar or even superior to advanced research instruments. However, little is known about the accuracy of their energy expenditure estimates. Here, we assessed their performance against criterion measurements in both controlled laboratory conditions (simulated activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
102
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 49 publications
10
102
4
2
Order By: Relevance
“…Additionally, only a portion of the day was spent in a free-living setting in our study, there was likely smaller variability in the data collected subsequently causing lower correlation coefficients than seen in the work of Dontje et al [12]. However, recent works have illustrated that CPAM's underestimate PA in free-living settings [14] and that the variability of these estimations is not consistent between CPAM models [13]. Collectively, available research suggests high or moderately-high reliability for most CPAMs and most dependent variables tested in free-living settings, supporting the use of these CPAMs during field-based PA monitoring [12].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Additionally, only a portion of the day was spent in a free-living setting in our study, there was likely smaller variability in the data collected subsequently causing lower correlation coefficients than seen in the work of Dontje et al [12]. However, recent works have illustrated that CPAM's underestimate PA in free-living settings [14] and that the variability of these estimations is not consistent between CPAM models [13]. Collectively, available research suggests high or moderately-high reliability for most CPAMs and most dependent variables tested in free-living settings, supporting the use of these CPAMs during field-based PA monitoring [12].…”
Section: Discussionmentioning
confidence: 67%
“…More recently, manufacturers have produced CPAMs which incorporate variables, such as heart rate or other variables (e.g., skin temperature), into their algorithms (e.g., Apple Watch and Fitbit Charge). Indeed, a recent study showed these multi-sensor CPAMs showed improved energy expenditure estimations compared to single-sensor CPAMs [13]. As multi-sensor CPAMs become more common, the reliability of their newer variables (e.g., heart rate) and the influence of newer variables on other preexisting variables (e.g., kcals) should be investigated as there is likely crosstalk between sensors.…”
Section: Discussionmentioning
confidence: 99%
“…The participant number of 40 patients was determined based on a literature study of comparable studies [5]- [8], [11], [13]. In most of these validation studies of wrist-worn health-tracking devices particpant numbers ranged from 20 to 60 patients.…”
Section: Patientsmentioning
confidence: 99%
“…Validation studies have been done to evaluate accuracy of HR, EE and other measurements in healthy subjects for a variety of fitness trackers [5][6][7][8][9][10][11][12][13][14][15][16][17]. Boudreaux et al [7] tested eight devices for accuracy of HR and EE measurements on healthy subjects and found that HR accuracy from wearable devices differed at different exercise intensities with an increasing underestimation of HR at higher exercise intensities.…”
Section: Introductionmentioning
confidence: 99%
“…La actividad física, definida como una actividad muscular que incrementa el gasto energético por encima de los valores de reposo (14), ha sido una variable de difícil medición debido a sus múltiples dimensiones y complejidad (15). Los cuestionarios para su evaluación se han convertido en una valiosa herramienta pues poseen buena relación costo-eficiencia que se explica por su alta flexibilidad en la obtención de la información y por su capacidad para estimar el gasto energético (16).…”
Section: Introductionunclassified